Individual and situational determinants of police force: An examination of threat presentation - Holmes, Stephen T. (American journal of criminal justice, 1998)
This study is based on previous research denoting the primary factors that influence officer decisions regarding the use of differing levels of force in police-citizen encounters. Using a totality of the circumstance approach, primary emphasis is directed toward explaining those factors that contribute to officers’ estimation of the perceived level of threat inherent in police-citizen encounters. Officers’ perceived level of threat presented by a suspect or the situational context of an encounter is important because in 1989, the Supreme Court in the Graham v. Conner decision mandated that the appropriate amount of force that can be utilized depends on the following four primary factors: the threat, offense severity, actual resistance offered, and whether the suspect is trying to escape custody. These criteria were tested and placed into a predictive model along with other indicators the literature has found to be correlated with situations in which police force is used more often. The findings suggest that while the threat presented to officers is important and related to the level of force that is deemed appropriate by the police profession, many additional elements must be taken into consideration when interpreting if an officer used force correctly.